Empowering E-Learning for English Literacy Development: Insights from Lecturers - Isma, Adi; Basri, Muhammad; Abduh, Amirullah; Putri, Andi Mega Januarti; Hustiana, Hustiana (JETAL: Journal of English Teaching & Applied Linguistic, 2024)
The integration of e-learning platforms in university settings has experienced notable growth, especially with the onset of the COVID-19 pandemic. This qualitative case study explored university lecturers' perceptions regarding the use of e-learning for teaching English literacy skills, specifically reading and writing. Semi-structured interviews were utilized for data collection with six lecturers from the English Department at Universitas Sulawesi Barat, Indonesia, who taught literacy courses during the 2022/2023 academic year. The findings revealed a spectrum of lecturers' experiences, beliefs, and attitudes toward e-learning-based literacy instruction. While initial challenges were encountered during the transition to online learning, the lecturers recognized benefits such as flexibility, efficient material sharing, and enabling remote assignments. However, connectivity issues, difficulties monitoring student progress, and the need for robust technological skills were identified as significant challenges. The lecturers advocated learner-centered, multimodal pedagogical approaches and emphasized the importance of balanced, blended learning that integrates both traditional classroom and online elements. The study highlights the potential of e-learning for enhancing English literacy education while underscoring the need to address infrastructural and pedagogical barriers.